KONSELING LINTAS BUDAYA DAN AGAMA: SUATU UPAYA PENANGANAN DISKRIMINASI TERHADAP MAHASISWA PAPUA - Fitria Husna; Sekar Ayu Aryani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The issue of discrimination, both racial and religious, in Indonesia remains prevalent despite various laws.. From various literature and data, it is illustrated that cases of discrimination in Indonesia are most often aimed at the people of Papua as well as students from Papua. This research will take a deeper look at the development of cases of racial and religious discrimination against students from Papua and offer a concept of multicultural and religious counseling on this issue. This research is a research with a qualitative approach to the type of library research (library research). The data sources in this study are books, documents, scientific articles, and previous research in national scientific journals. The internal data collection method used in this research is the documentation method with content analysis techniques. The results of this study show that Papuan students often receive various forms of discriminatory treatment from friends, the community, and even officials. They also felt various impacts, ranging from social, legal, political, and religious to psychological impacts. Counseling based on multi-cultures and religions with various services and approaches is a solution in efforts to prevent, reduce, and alleviate this problem.